Improving environmental risk assessments of chemicals: Steps towards evidence-based ecotoxicology. (July 2019) - Martin, Olwenn V.; Adams, Julie; Beasley, Amy; Belanger, Scott; Breton, Roger L.; Brock, Theo C.M.; Buonsante, Vito A.; Galay Burgos, Malyka; Green, John; Guiney, Patrick D.; Hall, Tilghman; Hanson, Mark; et al.
Graphical abstract: Unlabelled Image Highlights: 9 recommendations digest recent developments in regulatory environmental risk assessment. Efforts are necessary to make the translation of ecotoxicology into regulatory decisions more open and transparent. They require concerted and sustained action from a variety of sectors and stakeholders. Better evidence will lead to better decisions, sustainable innovation and a healthier environment.